The Influence of Race on Juvenile Justice Decision Making in Iowa: An Analysis of Involvement in Diversionary Programs at the Intake Stage - Arneil, Jayne M. (1993)
This thesis was undertaken to assess the influence of race on juvenile justice decision making. More specifically, the research examines the extent to which race and other extralegal factors as well as legal factors influence the use of release, informal adjustment, and further court processing via the petition, at the intake stage in juvenile justice proceedings. More importantly, this thesis focuses on the factors related to the type of diversion engaged in by youth receiving an informal adjustment at the intake stage. An informal adjustment is one of the most important alternatives available at the intake stage. It is a form of diversion where youth avoid further court processing by agreeing to participate in some types of services (e.g., informal probation, community service, payment of restitution). For the present analysis, the types of informal adjustments youth receive at the intake stage are defined as: whether or not probation is required; when probation is required, whether or not additional conditions are required; and when probation is not required, whether or not conditions are ordered by the juvenile court official. This study examines 3,157 white, black, and Hispanic youth referred to juvenile court in four counties in Iowa for the years 1980 through 1991. The analyses included information on the youth's referral offense, prior offenses, family, school, and case outcomes for both the prior and current involvement. The logistic regression results indicate that black youth are more likely to receive the most lenient and the most severe case dispositions at the intake stage compared with white youth and Hispanic youth. Furthermore, the findings suggest that black youth and Hispanic youth are more likely to receive less supervision within an informal adjustment than similarly situated white youth. The discussion focuses on reasons underlying the complex pattern of racial discrimination found in this study. This thesis and other studies examining race effects in the juvenile justice system may allow for the development of policy recommendations that may rectify the kinds of racial disparities that have been found to exist